A simple, safe and effective surgical technique for the treatment of post-traumatic parotid sialocoele - Asha'ari, Zamzil Amin; Razali, Mohd Sayuti; Leman, Wan Ishlah; Ahmad, Ashri (Universiti Sains Malaysia, 2014)
Post-traumatic parotid sialocoele is a subcutaneous extravasation of saliva from the parotid gland secondary to traumatic disruption of its duct or parenchyma. Currently, there is no consensus regarding the best therapy for parotid sialocoele, as it is resistant to conservative management. The present paper puts forward a relatively simple, safe and effective technique for the treatment of parotid sialocoele, specifically a peroral drainage technique. The results justify our recommendation to use this approach for the treatment of sialocoele.